Satellite Glial Cells: Morphology, functional heterogeneity, and role in pain - Andreeva, Daria; Murashova, Lada; Burzak, Nikita; Dyachuk, Vyacheslav (Frontiers in Cellular Neuroscience, 2022)
Neurons in the somatic, sympathetic, and parasympathetic ganglia are surrounded by envelopes consisting of satellite glial cells (SGCs). Recently, it has become clear that SGCs are highly altered after nerve injury, which influences neuronal excitability and, consequently, the development and maintenance of pain in different animal models of chronic pain. However, the exact mechanism underlying chronic pain is not fully understood yet because it is assumed that SGCs in different ganglia share many common peculiarities, making the process complex. Here, we review recent data on morphological and functional heterogeneity and changes in SGCs in various pain conditions and their role in response to injury. More research is required to decipher the role of SGCs in diseases, such as chronic pain, neuropathology, and neurodegenerative diseases.